Immunisation of dogs, hamsters and guinea pigs against Rhipicephalus sanguineus using crude unfed adult tick extracts - Bechara, G. H. [UNESP]; Szabó, M. P J; Mukai, L. S. [UNESP]; Rosa, P. C S [UNESP] (Elsevier, 1994)
Naive experimental groups of dogs, hamsters and guinea pigs were inoculated three times subcutaneously with unfed adult extract of the tick Rhipicephalus sanguineus and challenged with adult R. sanguineus to evaluate resistance. The acquisition of resistance was based on alterations of some reproductive and feeding performance parameters of female ticks such as female and egg mass weights, engorgement, pre-oviposition and incubation periods, larval hatchability rate and efficiency rates of female ticks in converting their food reservoir to eggs and larvae. Dogs did not develop resistance under these experimental conditions; guinea pigs and hamsters, to a lesser extent, acquired an effective immunity to ticks as demonstrated by the impairment of the reproductive and feeding performance. However, the resistance induced by inoculation of the extract in the rodents seemed not to be as efficient as that induced by successive infestations.
Keywords: quil a; saponin; vaccine; animal experiment; dog; guinea pig; hamster; host resistance; immunization; infestation; nonhuman; subcutaneous drug administration; tick; Animal; Dog Diseases; Dogs; Female; Guinea Pigs; Hamsters; Male; Support, Non-U.S. Gov't; Tick Infestations; Ticks; Vaccination; Acari; Animalia; Canis familiaris; Cavia; Cavia porcellus; Cricetinae; Rhipicephalus sanguineus; Rodentia; Sus scrofa